2021
DOI: 10.1007/s12029-021-00616-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Neutrophil-Lymphocyte Ratio and Platelet-Lymphocyte Ratio in Metastatic Colorectal Cancer

Abstract: There are many studies on biomarkers for prognosis in the treatment of metastatic colorectal cancer.Neutrophil-lymphocyte radio (NLR) and Platelet-lymphocyte radio (PLR) are of interest with studies revealing the relationship between in ammatory biomarkers and cancer. Our study is a retrospective le study and the contribution of NLR and PLR to progression-free survival (PFS) and overall survival(OS) before rst line chemotherapy was investigated regardless treatment. The cut off values of NLR and TLR were deter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…9 For decades, numerous studies have confirmed that inflammation plays an important role in cancer initiation, progression and metastasis. 10 Furthermore, inflammatory markers, such as neutrophil-to-lymphocyte ratio (NLR), platelet-tolymphocyte ratio (PLR), systemic immune inflammation index (SII), and systemic inflammation response index (SIRI), have been employed to predict the prognosis of breast, 11 lung, 12 pancreatic, 13 and cervical 14 cancers, among others. Previous studies have also suggested that high NLR, PLR, SII, and SIRI are significantly associated with poor prognosis in various malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…9 For decades, numerous studies have confirmed that inflammation plays an important role in cancer initiation, progression and metastasis. 10 Furthermore, inflammatory markers, such as neutrophil-to-lymphocyte ratio (NLR), platelet-tolymphocyte ratio (PLR), systemic immune inflammation index (SII), and systemic inflammation response index (SIRI), have been employed to predict the prognosis of breast, 11 lung, 12 pancreatic, 13 and cervical 14 cancers, among others. Previous studies have also suggested that high NLR, PLR, SII, and SIRI are significantly associated with poor prognosis in various malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-five of the included records reported that overall survival (OS) of CRC patients with high PLR levels was significantly shorter than for those with low PLR levels ( 11 15 , 17 , 19 27 , 29 – 31 , 34 , 35 , 46 50 ). Pooled analysis of OS revealed significant differences and moderate heterogeneity between the high and low PLR groups in the random-effect model (HR = 1.40, 95% CI = 1.21–1.62, P < 0.00001, Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the relationship between the PLR and CRC remains controversial. Some studies reported that an elevated PLR was an independent adverse prognostic factor in patients with CRC (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), yet others showed that the PLR could not be a related prognostic biomarker of CRC (11,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, 12 articles including 1452 patients published between 2014 and 2021 were included in this meta-analysis. The characteristics of the included studies are summarized in Table 1 [ 21 32 ]. All included literatures are retrospective studies.…”
Section: Resultsmentioning
confidence: 99%